Higher Consumption of Fruit and Vegetables Is Associated With Lower Worries, Tension and Lack of Joy Across the Lifespan - Radavelli-Bagatini, Simone; Sim, Marc; Blekkenhorst, Lauren C.; Bondonno, Nicola P.; Bondonno, Catherine P.; Woodman, Richard; Dickson, Joanne M.; Harms, Craig; Magliano, Dianna J.; Shaw, Jonathan E.; Daly, Robin M.; Hodgson, Jonathan M.; et al. (Frontiers in Nutrition, 2022)
ABSTRACT Background and aims: Higher total fruit and vegetable (FV) intakes have been associated with lower perceived stress. However, the relationship of FV intake with domains of perceived stress is unclear. The aim of this cross-sectional study was to explore the relationship between consumption of FV and four perceived stress domains (worries, tension, lack of joy and demands) in a population-based cohort of Australian adults. Methods: Participants (n=8,640) were men and women aged ≥25 years from the Australian Diabetes, Obesity and Lifestyle (AusDiab) Study. Dietary intake was assessed using a 74-item validated Food Frequency Questionnaire. Perceived stress domains were determined using a validated 20-item version of the Perceived Stress Questionnaire, with higher scores representing higher perceived stress. Cut-offs for high perceived stress domains were obtained from the highest quartiles of each domain for each sex. Multivariable-adjusted logistic regression was performed to investigate cross-sectional associations. Results: The mean age of participants (50.1% females) was 47.8 (SD 15) years. Those with higher intakes of FV, combined and separately, had a significantly lower odds (16-36%) for higher worries, tension and lack of joy, independent of other lifestyle factors. Conclusion: In Australian adults, higher consumption of FV was associated with lower odds of worries, tension and lack of joy. Following the dietary guidelines for the recommended intake of FV may help improve feelings of worries, tension and lack of joy, which are linked to mental health problems.